Phosphorus fractions in fallow systems of West Africa: effect of residue management - Tian, G.; Kolawole, G.O.; Tijani-Eniola, H. (Springer, 2004)
The effects of burning, incorporation and surface mulching after one year of natural regrowth (NF) and Pueraria cover crop fallows on soil P fractions and maize and cassava yields were assessed. Data were collected between 1998 and 2000 as part of an on-going long-term fallow management trial established in 1989 at the International Institute of Tropical Agriculture (IITA), Ibadan, in the derived savanna zone of southwestern Nigeria. After NF in 1998, burning temporarily increased resin- (63%) and NaOH- (19%) extractable inorganic P fractions when compared with mulching and incorporation. Organic P and total extractable P decreased as the season progressed. Fallow systems and residue management options had no consistent and significant effect on P fractions. For both years after NF, and in 1998, after Pueraria fallow, residue management options had no significant effect on cassava yield. However, in 1999 (wetter year), compared with burning and surface mulching, incorporation of Pueraria fallow residues improved maize and cassava yields. Similarly, maize yield was improved in 1999 with incorporation of NF residues. Maize yield increases due to incorporation of NF residues were 23% compared with burning and 49% compared with mulching. Maize yield increases due to incorporation of Pueraria residues were 37% compared with burning and 47% compared with mulching. Cassava yield was increased by 31% compared with burning and by 26% compared with mulching. Longer period of time may be required to assess whether differences in soil P fractions and crop yields will occur between fallow systems.